PENGARUH PERMAINAN SUMUR KREATIF TERHADAP KEMAMPUAN MENGENAL BENTUK-BENTUK GEOMETRI PADA ANAK USIA 5-6 TAHUN DI TK AISYAH KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Ayu Soraya; Rita Kurnia; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to know the influence of the game creative well to the ability to know geometry forms in children aged 5-6 years in the TK Aisyah of Rambah Sub-district Rokan Hulu District. This research aims to know the game of creative wells can improve the ability to recognize geometry in children aged 5-6 years in the TK Aisyah of Rambah Sub-district Rokan Hulu District. The samples in this research are children aged 5-6 years in the TK Aisyah of Rambah Sub-district Rokan Hulu District, which amounted to 17 children. The method used in this research is an experiment to see the influence between freely binding variables. The data collection techniques used are observation and poll. This data analysis technique is done by statistic T-Test technique with the help of SPPS Windows ver. 17.0 Technique statistic T-Test used to test the difference before and after treatment. From the research results before the treatment of creative well games there is the ability to know Geometric forms in children aged 5-6 years with a percentage value 42.22% and after a creative well-being treatment is a value of 77.52%. Based on the hypothesis test showing statistical test scores As of-28.918 the two-party test means absolute price, so the value (-) is not used (Sugiono,2010) so Thinung (28.918) because of the value of Sig. 2-tailed = 9.00 < 0.05. Then researchers can conclude that there is an influence to know the forms of geometry that are very significant after the game of creative wells. Key Words: Game Creative Well, Ability to Know Geometry